Plug-assisted retrograde transvenous obliteration via gastrocaval shunt for the gastric variceal bleeding: A case report. Issue 49 (10th December 2021) - Jang, Joo Yeon; Jeon, Ung Bae; Kim, Jin Hyeok; Kim, Tae Un; Ryu, Hwaseong; Cho, Mong; Hong, Young Mi; Yoon, Ki Tae
Abstract: Rationale: Most gastric varices at the fundus drain into the left renal vein via the gastrorenal shunt (80–85% of cases) or the inferior vena cava via the gastrocaval shunt (10–15%). Therefore, plug-assisted retrograde transvenous obliteration (PARTO) is usually performed via a gastrorenal shunt. Here, we report a case of gastric varix treated with PARTO via a gastrocaval shunt. Patient concerns: A 46-year-old woman with hepatitis B virus and liver cirrhosis visited the emergency room in our hospital with the main symptom of hematemesis and hematochezia. Diagnoses: Endoscopy and computed tomography (CT) revealed a gastric varix and thrombotic-occluded transjugular intrahepatic portosystemic shunt (TIPS) stent. Interventions: The patient underwent PARTO via a gastrocaval shunt to manage gastric variceal bleeding after failed TIPS revision. Outcomes: On CT, the gastric varix completely disappeared. The patient did not experience any additional bleeding events. Lessons: PARTO via a gastrocaval shunt is safe and effective.